Developmental profiles : - Allen, K. Eileen (Thomson Delmar Learning, 2007)
In a concise, point-by-point format, Developmental Profiles: Pre-birth through Twelve, 5e outlines the major characteristics for each of the domains in child development. With coverage of developmental profiles expanded to include middle childhood, each section highlights the daily routines and patterns of children so readers understand the nature of development and can translate emerging skills into everyday behavior. Updated information about prenatal care and brain research is presented, and critical safety concerns are identified with suggestions for appropriate adult supervision at each developmental stage. Tips assist readers in promoting children’s curiosity and learning, and case studies improve understanding and allow readers relate the content to real-life situations. Web resources for professional organizations also provide additional information for further consideration of child development.